Comparing ball speed and ball spin of tennis serve between game situation and practice in collegiate male tennis players - Takahashi, H.; Okamura, S.; Kashiwagi, R.; Numata, K.; Murakami, S. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: We introduced new technology system of tracking ball movement in tennis, called Trackman tennis radar (Trackman Inc., Denmark). The accuracy of Trackman data was verified about ball speed and ball spin (Murakami et al., 2016). The purpose of this study was to investigate ball speed and ball spin of tennis serve of male collegiate players. We focused on comparing those data between game situation and practice. Methods: Participants of this study was 14 male collegiate tennis players. They were divided into two groups: high ranked players (HRP) and low ranked players (LRP). Trackman tennis radar was used to collect data of expenmental matches by participants and practice sessions. Results: Regardless of groups, ball speed of 1st serve and 2nd serve in practice session was significantly faster than in game situation. Ball spin of 1st serve in game situation was significantly higher than in practice session. HRP showed that ball spin of 2nd serve in game situation was significantly lower than in practice session. LRP also showed no significant differences in ball spin of 2nd serve between game situation and practice session (Fig 1). Conclusion: Players selected safety serve to avoid errors in game situation. It also indicated that players showed slower swing speed on 2nd serve in game situation rather than practice session. It is considered they had skill problem on 2nd serve.